Experimental Characterization of 2 × 2 Electronically Reconfigurable Polarization Converter Unit Cells at X-Band - Biswarup Rana; In-Gon Lee; Ic-Pyo Hong (International Journal of Antennas and Propagation)
In this paper, an electronically reconfigurable polarization converter unit cell operating at X-band is proposed. The polarization converter unit cell consists of a passive patch, a phase shifter, and an active patch. There are two PIN diodes on the active patch. By switching the bias conditions of those PIN diodes, an electronically reconfigurable polarization converter is conceived. Both the passive and active patches are circular, and there are circular types of slots on both patches to enhance the operating bandwidth. To compensate for the capacitance introduced by PIN diodes, an equivalent capacitance structure is introduced on the active patch. 2 × 2 unit cells are designed to check the performance of the unit cell for polarization conversion applications. In addition, a novel type of experimental characterization technique is proposed to check the performance of polarization conversion using 2 × 2 unit cells. Two WR-90 waveguide sections, two rectangular to square sections, and a power supply are taken for the measurements. The rectangular to square waveguide transition section is designed in such a way so that 2 × 2 unit cells can be perfectly adjusted on the transition section and the performance of the 2 × 2 unit cells can be measured. The simulation results of the 8 × 8 array are also added to a miniaturized X-band horn antenna to check the performance of the overall array.